Epitope-Based Vaccine of a Brucella abortus Putative Small RNA Target Induces Protection and Less Tissue Damage in Mice - Oliveira, Karen Cristina; Brancaglion, Gustavo Andrade; Santos, Natália C. M.; Araújo, Leonardo P.; Novaes, Evandro; Santos, Renato de Lima; Oliveira, Sergio Costa; Corsetti, Patrícia Paiva; de Almeida, Leonardo Augusto (Frontiers in Immunology, 2021)
Brucella spp. are Gram-negative, facultative intracellular bacteria that cause brucellosis in humans and animals. Currently available live attenuated vaccines against brucellosis still have drawbacks. Therefore, subunit vaccines, produced using epitope-based antigens, have the advantage of being safe, cost-effective and efficacious. Here, we identified B. abortus small RNAs expressed during early infection with bone marrow-derived macrophages (BMDMs) and an apolipoprotein N-acyltransferase (Int) was identified as the putative target of the greatest expressed small RNA. Decreased expression of Int was observed during BMDM infection and the protein sequence was evaluated to rationally select a putative immunogenic epitope by immunoinformatic, which was explored as a vaccinal candidate. C57BL/6 mice were immunized and challenged with B. abortus, showing lower recovery in the number of viable bacteria in the liver, spleen, and axillary lymph node when compared to non-vaccinated mice. The vaccinated and infected mice showed the increased expression of TNF-α, IFN-γ, and IL-6 following expression of the anti-inflammatory genes IL-10 and TGF-β in the liver, justifying the reduction in the number and size of the observed granulomas. BMDMs stimulated with splenocyte supernatants from vaccinated and infected mice increase the CD86+ marker, as well as expressing greater amounts of iNOS and the consequent increase in NO production, suggesting an increase in the phagocytic and microbicidal capacity of these cells to eliminate the bacteria.